Assessing the level of mental skills among young athletes at different stages of physical training in sports radio direction-finding - Zelenskiy, K.G.; Ponomarev, G.N.; Kostyuchenko, V.F.; Zverev, V.D. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop mental skills at various stages of the long-term training of young athletes in sports radio direction-finding. Methods and structure of the study. The research was conducted during training sessions involving 95 athletes from the Russian Federation’s youth national team in sports radio direction-finding, competing in the young men’s, young women’s, junior men’s and junior women’s age groups, including 12 Masters of Sport, 31 athletes holding a first-class rank and the title of Candidate Master of Sport, 41 athletes holding third- and second-class ranks, and 11 athletes holding a youth rank. The athletes were asked to respond to 48 statements, which assessed the level of development of 12 different mental skills on a 7-point scale. Results and conclusions. It has been established that, throughout the entire long-term training process for both young men and junior men, as well as young women and junior women, mental skills – specifically ‘self-confidence’ and ‘anxiety management’ – are of the utmost importance.